Limit cycle oscillations measurements with Langmuir and ball-pen probes on COMPASS. (3rd October 2018) - Grover, O.; Seidl, J.; Refy, D.; Adamek, J.; Vondracek, P.; Tomes, M.; Junek, P.; Hacek, P.; Krbec, J.; Weinzettl, V.; Hron, M.; Zoletnik, S.
Abstract: This contribution presents the experimentally observed edge plasma evolution during limit cycle oscillations (LCO) measured with a new Langmuir and ball-pen multi-pin probe head at the COMPASS tokamak. The observed LCO regime modulates the intensity of density fluctuations, radial electric field E r and intensity of emission with a frequency 3–5 kHz. The density fluctuations grow after E r decreases in strength which appears to be strongly correlated with the evolution of the pressure gradient . The magnetic signature of the LCO shows a left–right asymmetry with propagation from the low to high field side. High-frequency (above 100 kHz) precursor-like oscillations are observed as well.